Serangan Ulat Jengkal (Hyposidra talaca Wlk.) Pada Bibit Pakoba (Syzygium luzonense (Merr.) Merr.) Di Persemaian - Hanif Nurul Hidayah; Arif Irawan; Illa Anggraini (Agrologia, 2017)
Obstace of pakoba (Syzygium luzonense (Merr.) Merr.) cultivation in nursery is  twig caterpillar (Hyposidra talaca WLK) attacks. The Pest symptoms was holes in the leaves especially young leaves; twig caterpillar enable to attack all leaves of pakoba seed. Severe attacks cause death of seedlings. There are five blocks in pakoba nursery that were observed; 1014 pakoba seedlings were grown in these blocks. The average percentage of twig caterpillar’s attack was quite high, reached 49.34%. Twig caterpillar has been controlled by integrated pest management. Chemical control to decrease twig caterpillars attack in nursery has been done by using half dose of insecticide profenofos.